FEATURES OF INFORMATION SECURITY IN THE EDUCATION SYSTEM OF THE REPUBLIC OF UZBEKISTAN (Academicia Globe: Inderscience Research, 2021)
The article analyzes the features of ensuring information security in the education system of the Republic of Uzbekistan from a socio-philosophical point of view. Also, the use of teaching aids in the higher education system - natural or visual visual materials in the classroom, in particular the subject, diagram, diagram, drawing, etc. Demonstration training equipment, tutorials, and the use of evidence on the topic, including quotes, definitions, rules, formulas, etc., as well as email, Internet, e-books, multimedia, distance learning, via video conferencing and other similar information in detail clarifies the spiritual and ethical aspects of effective use of funds.